Redução do tempo de compostagem de resíduos agroindustriais: efeito nos parâmetros de controle e na qualidade do composto final - Chiarelotto, Maico (2018)
The composting of agro-industrial waste from the production broiler helps minimizing the environmental, economic, and social impacts caused by such waste. In addition, the final product is an organic compost which can be used in vegetable production. The reduction of the time of stabilization of this waste is linked to the optimization of the conduction of the composting process, through the control and monitoring of physical-chemical parameters and the use of residues of urban tree trimmings, as bulking agent and carbon source. The reduction of composting time can consequently lead to a reduction in production costs, reducing the area required at the plant, as well as lower costs with fuel and labor. Therefore, the objective of this study was to determine the effects of the reduction of composting time on the main process control parameters and on the variables of interest for the agricultural use of the organic compost. The times of the stabilization process evaluated were 35, 63, and 95 days. The effects of time reduction, as well as the quality of the final compost in the stages of stabilization, maturation, and storage, were determined by the following parameters: reduction of mass, volume and organic matter, temperature, pH, EC, losses of N, P, and K, CEC, CEC:TOC ratio, carbon, phosphorus, potassium and soluble polyphenols, and FTIR. With the aid of the statistical techniques of comparison of averages and analysis of main principal components, it was possible to infer about the feasibility of the production of organic compost stable in 35 days of process, presenting CEC of 55.6 cmol kg-1, soluble carbon of 1.00 % and germination index of 140.9%. In addition, the characteristics of the final composition obtained at the 35-day process, are in accordance with the requirements defined by the Brazilian Ministry of Agriculture Livestock and Supply. It was concluded that the reduction of the stabilization time to 35 did not adversely affect the control parameters of the agroindustrial waste degradation process. All the organic compost produced in 35, 63, and 95 days of process presented characteristics of stabilized compost, being suitable for agricultural use.